2021
DOI: 10.1038/s41598-021-84804-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of grey matter changes and their behavioral characterization in patients with alcohol use disorder

Abstract: Alcohol Use Disorder (AUD) is associated with reductions in grey matter (GM) volume which can lead to changes in numerous brain functions. The results of previous studies on altered GM in AUD differ considerably in the regions identified. Three meta-analyses carried out between 2014 and 2017 yielded different results. The present study includes the considerable amount of newer research and delivers a state-of-the art meta-analysis in line with recently published guidelines. Additionally, we behaviorally charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 99 publications
(110 reference statements)
3
9
0
Order By: Relevance
“…In summary, the above examples point towards an association of WM changes in AUD patients identified by this meta-analysis and several behavioral impairments. Together with previously reported GM reductions in AUD [ 18 ], they may explain the deterioration of a wide range of motor, cognitive, affective, and perceptual functions in individuals with AUD. However, the behavioral interpretation of our results is still speculative as it is based on a few single studies and as we could not apply a data-driven approach that is comparable to the workflows via the BrainMap database for GM data [ 79 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In summary, the above examples point towards an association of WM changes in AUD patients identified by this meta-analysis and several behavioral impairments. Together with previously reported GM reductions in AUD [ 18 ], they may explain the deterioration of a wide range of motor, cognitive, affective, and perceptual functions in individuals with AUD. However, the behavioral interpretation of our results is still speculative as it is based on a few single studies and as we could not apply a data-driven approach that is comparable to the workflows via the BrainMap database for GM data [ 79 ].…”
Section: Discussionsupporting
confidence: 74%
“…Structural brain alterations in AUD have been investigated in a large number of neuroimaging studies. Regarding GM changes, several meta-analyses highlighted specific patterns of reduced regional brain volume or density [ 16 18 ]. In recent years, the number of studies investigating the macro- and microstructure of WM by magnetic resonance imaging (MRI) methods has also increased.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous consumption of alcohol in high levels can lead to long-term functional changes such as impairments in visuo-spatial functioning [ 49 ]. Functional impairments in alcohol abuse can be explained by the changes in grey matter structure, resulting from the neurotoxicity of alcohol in chronic high consumption patterns [ 50 ]. Several studies have showed that in alcohol abuse patients the grey matter volume reduced as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Saito et al reported changes in the count of glial cells after chronic ethanol exposure [ 52 ]. Together, these findings indicate that alcohol consumption causes a decline in grey matter size in certain brain regions and has effects on the behavioral depiction of these brain areas that may lead to cognitive impairment [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, meta-analysis study on the structural findings of AUD using an effect-size based meta-analytical approach demonstrated significant GM reductions in the corticostriatal-limbic circuits including the key areas of the triple networks, such as DLPFC, hippocampus, bilateral insula, and ACC compared to healthy controls ( 9 ). Another study applying a different methodology (i.e., Anatomical Likelihood Estimation) also found gray matter reduction in the insula, ACC, and DLPFC, and demonstrated the association between volume reduction and functional impairment including cognition, emotion, and perception ( 28 ). This finding suggests that the gray matter reduction of the areas in the triple networks could be associated with cognitive and affective impairment observed in patients with AUD.…”
Section: Introductionmentioning
confidence: 98%